ALIGNMENT OF A CCD DEVICE INTO THE IMAGE PLANE - Ábrahám, György (Periodica Polytechnica Mechanical Engineering, 1987)
Methods and instruments for the alignment of the optical sensors in the spacelabs Vega I. and II. are shown in this article. The determination of the best position of the CCD plane had become more exact applying OTF measurements in the focal plane.